VOYAGER: an international consortium investigating the role of human papilloma virus and genetics in oral and oropharyngeal cancer risk and survival - Gormley, M; Adhikari, A; Dudding, T; Pring, M; Hurley, K; Macfarlane, G J; Lagiou, P; Lagiou, A; Polesel, J; Agudo, A; Alemany, L; Ahrens, W; et al. (medRxiv, 2025)
Head and neck cancer (HNC) is the sixth most common cancer globally. Incidence and survival rates vary significantly across geographic regions and tumor subsites. This is partly due to differences in risk factor exposure, which includes tobacco smoking, alcohol consumption and human papillomavirus (HPV) infection, alongside detection and treatment strategies. The VOYAGER (human papillomaVirus, Oral and oropharYngeal cAncer GEnomic Research) consortium is a collaboration between five large North American and European studies which generated data on 10,530 participants (7,233 cases and 3,297 controls). The primary goal of the collaboration was to improve understing of the role of HPV and genetic factors in oral cavity and oropharyngeal cancer risk and outcome. Demographic and clinical data collected by the five studies were harmonized, and HPV status was determined for the majority of cases. In addition, 999 tumors were sequenced to define somatic mutations. These activities generated a comprehensive biomedical resource that can be utilized to answer critical outsting research questions to help improve HNC prevention, early detection, treatment, and surveillance.
Keywords: oral cancer; human papilloma virus; survival; risk factors; oropharyngeal cancer; Head and neck cancer